Questions scientifically-methodical providing of forming readiness of future engineers-teachers to the use health of saving technologies in professional activity - Luk'yanova Y.S (Kharkov National Pedagogical University, 2010)
The ways of improvement of maintenance are rotined to professionally-pedagogical preparations of future engineers-teachers to the use health of saving technologies. Educational disciplines are complemented to professionally-practical and humanitarian preparation questions educational health of saving technologies. The necessity of observance of basic terms of assistance the maintenance of health of students is rotined for an educational process: The computer-integrated special course of systematization of knowledge and abilities of the use is developed health of saving technologies in professional activity.